2012
DOI: 10.5713/ajas.2012.12020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Potential Acid Production Value on Productivity in Dairy Cows

Abstract: This study was conducted to estimate the potential acid production value (PAPV) of major diets and to determine the relationship between dietary PAPV and dairy production traits. Estimation of PAPV of major cattle feeds was based on an in vitro technique, which determined the degree of Ca dissociation from CaCO3. Data on feeds and production traits were collected on 744 multiparous lactating Holstein dairy cows from five different farms. Grains had high PAPV with variable protein sources and by-products. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the present study, the reduction in protozoal diversity could be attributed to the change in pH or the change in substrate as grain and concentrate diets often reduce microbial diversity (Wu et al, 2011 ; Belanche et al, 2012a ; Li et al, 2013 ; Fernandes et al, 2014 ; Kumar et al, 2015 ). Differentiating between the effects of the availability of different feed substrates and the acid-production potential of feeds (Kim et al, 2012 ) on rumen microbial diversity is challenging, especially as different feed substrates or formulations can cause varied amount of saliva production, which can buffer rumen fluid pH. In vitro investigation using fermentation chambers showed pH was a larger driver of fermentative ability than substrate; low pH reduced microbial fiber digestion, nitrogen circulation, and volatile fatty acid production, especially acetate and butyrate (Calsamiglia et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the reduction in protozoal diversity could be attributed to the change in pH or the change in substrate as grain and concentrate diets often reduce microbial diversity (Wu et al, 2011 ; Belanche et al, 2012a ; Li et al, 2013 ; Fernandes et al, 2014 ; Kumar et al, 2015 ). Differentiating between the effects of the availability of different feed substrates and the acid-production potential of feeds (Kim et al, 2012 ) on rumen microbial diversity is challenging, especially as different feed substrates or formulations can cause varied amount of saliva production, which can buffer rumen fluid pH. In vitro investigation using fermentation chambers showed pH was a larger driver of fermentative ability than substrate; low pH reduced microbial fiber digestion, nitrogen circulation, and volatile fatty acid production, especially acetate and butyrate (Calsamiglia et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the previous studies also rumen fluid was collected from a single fistulated cow, which was used for measuring dissimilary reduction of nitrate and nitrite in the bovine rumen [ 30 ]. Kim et al [ 31 ] also reported the dietary potential acid productions values, where rumen fluid was collected from a single fistulated cow. In the present investigation, concentrations of cyanotoxins (0.05, 0.5 and 5 μg/mL) incubated with rumen fluid are in correspondence to the sub chronic and acute doses of cattle announced by California Environmental Protection Agency [ 32 ].…”
Section: Discussionmentioning
confidence: 99%